Report of the Working Group on Employment Planning and Policy for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
During 2000-2007, the labour force is projected to grow at the rale of around 1.71%. In absolute term, 7 to 8 million persons are expected to join the labour fore on an avenge per year. Employment is projected to grow at the rate of 1.43% per annum when GDP grows at the rate of 6.5%. This means if the economy attains a growth rate of 6.5% per annum, a total number of 5 to 7 million employment opportunities on an average per annum may be created in the normal growth process.
Government of India, Planning Commission